Research Progress in the Treatment of Obese Polycystic Ovary Syndrome with Traditional Chinese Medicine - Wang, Yu; Su, Hongxia (Journal of Contemporary Medical Practice, 2024)
Polycystic ovary syndrome (PCOS) is a common endocrine disorder in gynecology, with a high clinical incidence, which seriously affects the quality of life of adolescent and reproductive age women. This article expounds the progress of traditional Chinese medicine treatment of obese polycystic ovary syndrome, considers phlegm dampness as its primary pathogenic factor, and takes tonifying kidney, invigorating spleen and soothing liver as the basic treatment principles, in order to provide reliable and effective reference for traditional Chinese medicine treatment of PCOS.